Proteomic Differential in-Gel Electrophoresis Analysis of Stigmatic and Stylar Proteins in Kiwifruit before and after Pollination - Qi, Xiujuan; Gao, Yongbin; Fang, Jinbao; Xu, Shankun; Chen, Jinyong; Gu, Hong; Zhang, Shaoling (Current Proteomics, 2014)
Background: Stigmatic and stylar proteins play a pivotal role in plant reproduction during pollination and fertilization. Methods: Total proteins from kiwifruit (Actinidia. Arguta L.) stigmatic and stylar have been extracted in our present study at two time points, before pollination and 10 h after pollination. Further, proteins were characterized and identified using fluorescence differential in-gel electrophoresis (DIGE), matrix-assisted laser-desorption / ionization Time of Fight / Time of Fight (MALDI-TOF / TOF), and bioinformatics technology. Meanwhile, the growth of kiwifruit pollen tubes in the style was observed under a fluorescence microscope. Ten hours after pollination, most pollen tubes reached the bottom of the kiwifruit style. Results: Twenty-four protein spots showed significantly differential expressions (ratio > 2.5) by using DeCyder 6.5 (Amersham Bioscience) analysis in our study. Of these 24 proteins, 18 proteins were specifically investigated through MALDI-TOF / TOF. Of these 18 proteins, eight protein candidates (spot No. 958, 1022, 1025, 968, 1088, 1058, 1087, and 1081) belong to the actinidin family, two of them (spot No. 911 and 907) belong to chitinase, and four protein spots belong to proline dehydrogenase (spot No. 1336), glutathione S-transferase (spot No. 1106), ATP synthase (spot No. 1100), and L-galactose-1-phosphate phosphatase (spot No. 977). The remaining four candidates (spot No. 895, 903, 1378, and 1345) are hypothetical proteins. Among these 18 significantly differentially expressed protein spots, six were up-regulated while 12 were down-regulated, when compared with stigmatic and stylar proteins before pollination. Conclusion: Most of the identified proteins may play an important role during kiwifruit pollination. But their putative functions during this stage remain to be further investigated.
Keywords: style